MODEL LOTRE ; STRATEGI PENETUAN SEWA BENGKOK DESA (Studi Fenomenologi Pada Desa Tawangrejo Kec. Wonodadi Kab. Blitar) - Diana Elvianita (Universitas Islam Balitar, 2016)
This Research aims to determine how the determination of“Bengkok– land leases used Tawangrejo Rural District of WonodadiBlitar? The method used is qualitative with phenomenologicalapproach. The results of this research The village governmentTawangrejo Wonodadi District of Blitar Using “Lotre Model– todetermine a “Bengkok– land tenants as the principle of justice andequity. this method intended for residents of the village can bealternately each year to hire a “Bengkok– land and residents can feelthe results of the village land